Animals in the Holy Quran Vol. 13 - Mohamed Akhiruddin Ibrahim; Azlina Mohamed Nor (Universiti Sains Islam Malaysia, 2022)
Animals were created by Allah with different characteristics and purpose. Obviosly, what differentiates us from animals is the fact that we were gifted with aql.